Trust architecture and reputation evaluation for internet of things - CHEN, Juan (Institutional Knowledge at Singapore Management University, 2019)
Internet of Things (IoT) represents a fundamental infrastructure and set of techniques that support innovative services in various application domains. Trust management plays an important role in enabling the reliable data collection and mining, context-awareness, and enhanced user security in the IoT. The main tasks of trust management include trust architecture design and reputation evaluation. However, existing trust architectures and reputation evaluation solutions cannot be directly applied to the IoT, due to the large number of physical entities, the limited computation ability of physical entities, and the highly dynamic nature of the network. In comparison, it generally requires a general and flexible architecture to manage trust in such a dynamic environment as IoT. In this paper, we present IoTrust, a trust architecture that integrates Soft Defined Network (SDN) in IoT, and a cross-layer authorization protocol based on IoTrust. IoTrust and the protocol together provide a new insight for research on trust management in the IoT. For trust establishment, we further propose a Behavior-based Reputation Evaluation Scheme for the Node (BES) and an Organization Reputation Evaluation Scheme (ORES). Both our theoretical analysis and simulation results validate the efficiency of BES and ORES.